Pemikiran Hukum Islam Perspektif Yusuf Al-Qardawi: Elastisitas Hukum Islam dan Moderasi Beragama - Rozi, Fathur; Sari, Abu (Mahad Aly Al Fithrah, 2025)
Yusuf al-Qardawi's Islamic legal thought is a form of contemporary ijtihad that emphasizes the elasticity of Islamic law and the principle of religious moderation (wasathiyyah). The background of this study is based on the need for Muslims to understand Islamic law in a more flexible context and relevant to changing times. Al-Qardawi proposed a legal approach that is not only based on texts alone, but also considers social, economic, and cultural aspects. The purpose of this study is to analyze the concept of elasticity of Islamic law according to Yusuf al-Qardawi and how this principle is implemented in various aspects of life, such as Islamic economics, family law, politics, and criminal law. In addition, this study also examines the role of moderation in religion as a solution to extremism and radicalism that often arise due to an understanding of Islam that is too rigid or liberal. Previous studies have shown that many studies have discussed al-Qardawi's thoughts from the aspects of Islamic law, sharia economics, and Islamic politics. However, this study focuses more on the integration between the elasticity of Islamic law and the concept of moderation that characterizes al-Qardawi's thoughts. This study fills the research gap by offering a comprehensive analysis of the relevance and application of these concepts in a contemporary context. The research method used in this study is a qualitative method with a descriptive-analytical approach. Data were collected through a literature study of Yusuf al-Qardawi's works, scientific articles, and other relevant secondary references. The analysis was conducted by examining how the concepts of Islamic legal elasticity and religious moderation are applied in various aspects of life. The results of the study show that Yusuf al-Qardawi's Islamic legal thinking has made a major contribution in presenting Islamic law that is more adaptive and relevant to the conditions of modern society. The concept of Islamic legal elasticity that he developed opens up a wide space for ijtihad so that Islamic law remains contextual and provides solutions to the problems of the people. The religious moderation that he promotes is also an important foundation in building a more inclusive and tolerant understanding of Islam.